Super Mario adventures - Takekuma, Kentaro, 1960- (Viz Media, LLC, 2016)
Collection of color comics featuring Super Mario video game characters Mario, Luigi, the diabolical Bowser, the imperiled Princess Toadstool, and Yoshi.